Meningkatkan Kinerja Tenaga Pendidik Melalui Kebijakan Penataan dan Pemerataan Guru di Kabupaten Semarang - Fatkuroji Fatkuroji (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2017)
The issue of imbalance in the availability of teachers in schools, whether as classroom teachers, or subject teachers continues to follow, without any concrete solutions starting at education, district, provincial and national levels. This research was conducted to find out about the policy of education office of Semarang Regency in improving, arranging and equity of teacher performance. The research type is qualitative research and case study. Technique of collecting data in this research is done by interview method, FGD, and document. Data analysis in this study by using, data reduction, data presentation, take conclusions and verification. Based on the results of the calculation of the needs of teachers seems to have been calculating the needs of class teachers and teachers census civil servants in schools directly addressed by the appointment of non-civil servant teachers. Almost all levels of education lack of teachers, and there are still some teachers who do not meet the standards of competence and there are still some teachers who do not meet the competency standards as well as the number of teachers entering retirement increase the number of teachers in the district of Semarang.